Dinamika Pengujian Undang-Undang Tindak Pidana Korupsi: Tantangan, Penolakan, Dan Arah Reformasi Hukum (Lembaga Pengembangan Kinerja Dosen, 2025)
The judicial review of Law Number 20 of 2001 in conjunction with Law Number 31 of 1999 on the eradication of corruption in Indonesia faces various dynamics, including legal, political, and social challenges. This study aims to identify the challenges arising in the judicial review process of corruption laws, particularly regarding the policy on the application of Article 2 Paragraph (1) and Article 3 of the Corruption Eradication Law (UU Tipikor), which have led to various issues. It also analyzes the forms of opposition from different parties and proposes legal reforms to enhance the effectiveness of judicial reviews. The findings reveal that the primary challenges include unclear legal norms, political interference, and social resistance. Forms of opposition often arise through judicial reviews, political pressures, and institutional resistance. To address these issues, legal reforms are needed, such as strengthening the legal framework, enhancing the independence of judicial institutions, and broadening public participation. This study contributes to enriching academic discussions on legal reform and anti-corruption efforts in Indonesia.